Everett Spring papers - Spring, Everett
Chiefly drafts and copies of Spring's essays on U.S. history and government as well as various scientific and philosophical topics. Also includes correspondence with his publishers, accounts of payments for his writings, scrapbooks of his published articles, and five volumes of the American Mutual Magazine.
U.S. Commerce Dept. employee.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Mutual magazine; Philosophy; Science; United States -- History; United States -- Politics and government; Public officials